2018
DOI: 10.1111/anu.12795
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein at two lipid levels on growth, gonadal development, body composition and liver metabolic enzymes of brown trout (Salmo trutta fario) broodstock

Abstract: This study was conducted to estimate the effects of dietary protein and lipid levels on the growth, body composition, gonadal development and activity of liver metabolic enzymes of the brown trout Salmo trutta fario broodstock. Ten diets were formulated containing five different protein levels (360, 390, 420, 450 and 480 g/kg) and two different lipid levels (90 and 180 g/kg). The experiment was a completely randomized 5 × 2 factorial design. The fish with an initial body weight of 462.53 ± 45.40 g were culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
3
9
1
Order By: Relevance
“…Moreover, when sh are offered diets with a protein content below the requirement level, they would consume more feed to gain su cient protein needed for supporting growth and metabolism while at optimum or higher dietary protein levels lesser diet would be needed. Our results revealed the enhancement of FE as protein and lipid levels increased which is consistent with studies on masu salmon [33], Manchurian trout [30], brown trout (Salmo trutta fario) [34], Japanese seabass (Lateolabrax japonicus) [7] and black seabass (Centropristis striata) [35]. Xu et al [30] showed that enhancing fat content of feed from 8 to 16% enhances PER in Manchurian trout at dietary protein levels of 40-45%.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, when sh are offered diets with a protein content below the requirement level, they would consume more feed to gain su cient protein needed for supporting growth and metabolism while at optimum or higher dietary protein levels lesser diet would be needed. Our results revealed the enhancement of FE as protein and lipid levels increased which is consistent with studies on masu salmon [33], Manchurian trout [30], brown trout (Salmo trutta fario) [34], Japanese seabass (Lateolabrax japonicus) [7] and black seabass (Centropristis striata) [35]. Xu et al [30] showed that enhancing fat content of feed from 8 to 16% enhances PER in Manchurian trout at dietary protein levels of 40-45%.…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, the activity of hepatic ALT was not affected by the dietary protein level, indicating that protein catabolism was the same irrespective of the dietary protein level. This observation is not in line with data reported by other authors, who described a positive relationship between amino acid degradation by hepatic ALT and dietary protein intake (Fernández et al, 2007; Gaye‐Siessegger et al, 2006; Wang et al, 2018). The unresponsiveness of the hepatic ALT enzyme to the different protein levels in this study may have been related to the fact that protease trypsin and chymotrypsin activities were enhanced by lower dietary protein levels.…”
Section: Discussioncontrasting
confidence: 76%
“…Although amino acids are the preferential energy substrate for fish (Jia et al 2017), it has been shown that an increase of non-protein energy (lipid oH carbohydrates) in the diet can reduce dietary amino acid catabolism in some fish (Fernández et al 2007, Enes et al 2008, Wang et al 2018). In the present study, the amino acid catabolism enzyme ALT was not affected by dietary lipid content changes.…”
Section: Liver Enzymesmentioning
confidence: 99%